Ferdydurke, czyli studium nad Formą – o kłopotach w recepcji Gombrowiczowskiego dzieła i o recepcie na prawidłowe jego odczytanie - Urbańska, Agnieszka (Postscriptum Polonistyczne, 2020)
The article aims to present one of the most popular yet at the same time often misunderstood novels by Witold Gombrowicz – Ferdydurke. The article claims that the most important motif in Gombrowicz’s works is the problem with Form and in Ferdydurke the writer tackles this very subject. This novel – though not very long – is a complex and rich analysis of Form related to human life. The concept of Form is the key to an adequate understanding of Ferdydurke: it justifies unusual formal strategies and linguistic means used by the writer. It also explains a complicated plot and proves that what used to be regarded as chaos is in fact an intended strategy used in a logical and consequential way. The article is addressed above all to those, who being unfamiliar with Gombrowicz’s creativity, regard it as strange and incomprehensible. It proves that at least in the case of Ferdydurke this is not true and it is worth reading Gombrowicz’s works once again, as the world created by the writer is fascinating and multidimensional.